Stock Liquidity and State Ownership: Evidence from the Banking Industry of Selected Asian Emerging Markets - Ai-Xin Lee; Chee-Wooi Hooy (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: Liquidity creation is deemed important in the emerging markets banking industry. It turns out to be more challenging when subject to ownership issues, particularly state ownership. The government possesses substantial ownership in many large banks in Asian emerging markets and has a significant effect on firms’ stock liquidity through trading activity. Hence, state ownership is a key determinant of stock liquidity. This paper investigates the effect of state ownership on stock liquidity in Asian emerging markets. Design/Methodology/Approach: Using the GMM panel regression model, this study examines a sample of 209 banks in Asian emerging markets including China, India, Indonesia, Malaysia, Pakistan, Philippines, South Korea, Taiwan, and Thailand from 2009 to 2018. For the robustness test, an alternative liquidity measure is conducted. Research findings: Results show that state ownership is positively related to stock liquidity, implying that the participation of the government provides investors’ confidence and perceives these stocks as value-enhancing stocks. However, this positive effect on stock liquidity turns out to be negative when the state ownership surpassed a certain threshold. Thus, this paper finds a non-linear inverse U-shaped relationship between state ownership and stock liquidity. Further analysis also shows that large banks tend to enjoy greater liquidity compared to smaller banks. Theoretical contribution/Originality: Unlike past studies that focus on other ownership structures, this study focuses on state ownership of large banks in emerging markets. This study contributes by collectively addressing the impact of state ownership on stock liquidity, with a focus on the banking industry in the Asian emerging markets context. Practitioner/Policy implications: The findings of this study can benefit investors, policymakers, and other stakeholders to better understand the impact of state ownership on stock liquidity. There are various implications in terms of investment decisions and corporate governance policies pertaining to corporate ownership structure. Research limitation: Future studies may consider conducting sub-samples using a different threshold of state ownership. Besides, this study focuses on the banking sector and hence the results may not be generalised.